Pengaruh Kompetensi Terhadap Kinerja Dengan Karakteristik Pekerjaan Sebagai Mediasi Di Dinas Pemberdayaan Masyarakat Desa Kabupaten Sampang - Subaidah Subaidah; Sri Mulyani; Chamariyah Chamariyah (Journal of Management and Creative Business, 2024)
Subaidah, 2023. The Effect of Competence on the Performance of Employees of the Village Community Empowerment Service in Sampang Regency which is mediated by work characteristics, Wijaya Putra University Postgraduate Program. This type of research is explanatory, the research approach used is quantitative, the research sample is 47 respondents. Data analysis uses SPSS and PLS analysis. The aims of this study were: 1) To analyze the influence of competence on the performance of the Village Community Empowerment Service employees in Sampang Regency; 2) To analyze the effect of competency on the job characteristics of the Village Community Empowerment Service employees in Sampang Regency; 3) To analyze the influence of job characteristics on the performance of employees of the Village Community Empowerment Office of Sampang Regency; 4) To analyze the indirect effect of competence on the performance of employees of the Village Community Empowerment Service in Sampang Regency which is mediated by job characteristics; The results of the study show that: 1) Competence has a significant effect on the performance of employees of the Village Community Empowerment Service in Sampang Regency with an original sample value of 0.320; 2) Competence has a significant effect on the job characteristics of employees of the Sampang District Village Community Empowerment Service with an original sample value of 0.326; 3) Job characteristics have a significant effect on employee performance with an original sample value of 0.367; 4) Competence has a significant indirect effect on the performance of employees of the Village Community Empowerment Service in Sampang Regency which is mediated by job characteristics with an original sample value of 0.319 and a p-value of 0.005.